Anti-Corruption Legal Management Framework in Iraq: Evaluating the Effectiveness of the Integrity Law - Ali, Ahmed Mustafa (Journal of Cultural Analysis and Social Change, 2025)
Evidently, administrative corruption in Iraq undermines public confidence, squanders resources, and hinders the sustainability of development efforts. Even after Iraq enacted the Integrity Law and established the Federal Commission of Integrity, persistent corruption issues within the government have raised doubts about the sufficiency of these laws. This study examines how the Integrity Law enhances the prevention of administrative corruption in Iraq, drawing insights from best practices in other nations. I analyzed translated laws from Iraq, the United Nations Convention against Corruption (UNCAC), and official reports produced by Transparency International, the World Bank, UNDP, and the OECD. More than 30 reviewed studies were examined to ensure comprehensive coverage of the legal, institutional, and political dimensions of anti-corruption. Research indicates that while the law promotes strong governance, its effective enforcement is hampered by inadequate coordination among institutions and political pressure. The study emphasizes the need for more rigorous enforcement, enhanced protection for whistleblowers, and alignment of regulations with international standards. Reforms are essential to bolster accountability and foster governance within Iraq’s public sector.